Influence of pre-strain on the strain rate response of Ni-Ti shape memory alloy / Nur Aliah Mohd Khairi...[et al.] - Mohd Khairi, Nur Aliah; Ibrahim, Azmi; Ab Hamid, Hanizah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The presence of Shape Memory Alloy (SMA) in civil engineering fields offered a lot of advantages to the industries. The superiority of SMA is when the material has the ability to remember its previous shape after it has deformed and it will return back to its original defined shape when it is subjected to heat. Nickel-Titanium (Ni-Ti) is known as the finest alloy among SMA groups. In this research, the influence of pre-strain on the mechanical behavior of Ni-Ti shape memory alloy bars were examined in room temperature with concerns of a different strain rates, which are 5.5x10-4 s-1 and 1x10-3 s-1. Each of the test piece was pre-strained at level 5ξ, 10ξ and 15ξ. A quasi-static tensile test was carried out on heat treated Ni-Ti by using a Universal Testing Machine to observe the Ni-Ti stress-strain response. The results show tensile strength of Ni-Ti increased after applying pre-strain and heat treatment at 500°C. However, it is observed tensile strength of Ni-Ti started to drop after pre-strained at 15ξ. So, it indicates that strain ageing of Ni-Ti bars at a large strain becomes practically irrelevant, even though Ni-Ti is a super-alloy. Furthermore, Ni-Ti is a strain rate dependent material where the strength increases at a higher rate. Thus, it was found Ni-Ti exhibited yield strength differently where the yield strength increases as the strain rate decreases.